Upper critical field in superconductors and the uncertainty principle: Upper limit to the maximum slope of Hc2 - Luzuriaga, J. (American Physical Society, 1990)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina